Compressive buckling strength of extruded aluminium alloy I-section columns with fixed-pinned end conditions. (October 2017) - Wang, Y.Q.; Yuan, H.X.; Chang, T.; Du, X.X.; Yu, M.
Abstract: The compressive buckling behaviour of extruded aluminium alloy I-section columns with fixed-pinned end conditions has been experimentally and numerically investigated in this study. A total of 11 column tests, involving two heat-treated aluminium alloys – 6061-T6 and 6063-T5, were carried out to acquire the compressive buckling strengths. Prior to the column tests, material properties of the two aluminium alloys were determined from tensile coupon tests, while the initial local and global geometric imperfections were separately measured by means of experimental techniques. By using the ABAQUS software package, finite element (FE) models that could account for material non-linearity and initial geometric imperfections were developed. The FE models were further validated against the test results, enabling reliable simulation of the compressive buckling behaviour of the tested columns with fixed-pinned end conditions. Based on the obtained test and numerical results, the calculation methods in the current design standards, including the European, Chinese, American and Australian/New Zealand specifications, were all assessed. It was shown that the design provisions in all the four standards provided relatively conservative strength predictions, especially for the aluminium alloys with more pronounced strain hardening capacity. Highlights: Column buckling tests on 11 extruded aluminium alloy I-sections with fixed-pinned end conditions. Validated FE modelling of the compressive buckling behaviour. Evaluation of exiting design standards using the obtained test and numerical results.